Collaboration expectation gaps, transparency and integrated NPD performance: A multi-case study. Issue 4 (October 2022) - DeCampos, Hugo A.; Fawcett, Stanley E.; Melnyk, Steven A.
Abstract: This paper explores the implications of what happens when a buying firm's desired and realized levels of collaboration differ in the context of an integrated new product development (NPD) project. Using analysis of six case studies, we observe varying levels of such collaboration expectation gaps (CEG) and conclude that these gaps can impact NPD project performance. In addition, collaboration transparency is established when a firm and its partner firm comprehend the factors (benefits, risks, costs) that motivate collaboration between them. We observe that the presence of collaboration transparency impacts the emergence of CEG across the phases of an NPD project. These findings extend existing theory on buyer-supplier relationships in NPD projects and introduce CEG and collaboration transparency as important concepts in understanding improved collaboration performance. Highlights: Differences between desired and actual levels of collaboration result in collaboration expectation gaps (CEG). The size of these gaps can negatively impact joint NPD project performance. Collaboration transparency is the degree of understanding of the factors and motivations for the collaboration. Lack of collaboration transparency can negatively impact joint NPD project performance.